Kilka uwag o podstawach prawnych ograniczeń dostępu do broni palnej w Polsce - Mikowski, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The paper outlines the legal grounds for access to firearms in Poland, taking into account the current trends related to the government’s obligation to provide security to citizens. The article includes an analysis of both the constitutional principles and the applicable legislation in force, along with secondary legislation Regulations, is aimed at the clarification of the importance of the restrictions being introduced by the legislature in this field. The preventive and conservative approach of the legislature towards the expectations of some circles of stakeholders justifies the statement that the admission of firearms to be marketed is a strictly regulated exception to the principle of restricting access to firearms, which significantly contributes to the increased sense of security among citizens, especially in the light of current developments in the world.
Keywords: firearms; firearms permit; firearms access regulation